Karakteristik limbah pertanian dan dampaknya: Mengapa pengelolaan ramah lingkungan penting? - Arista, Nor Isnaeni Dwi (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Agricultural waste is a significant by-product of the agrarian sector, with the potential for substantial environmental and economic impacts. This study aims to examine the characteristics of organic agricultural waste and analyze its effects on the environment, both in terms of threats and its potential utilization. Method: This study employs a systematic literature review method. The literature search focuses on articles discussing agricultural waste, its characteristics, and its environmental impacts. Findings: The results show that agricultural waste has diverse characteristics based on fiber composition, physical form, and protein content. The main threats from agricultural waste include water pollution due to nutrient runoff and greenhouse gas emissions, especially methane. However, this waste also holds significant potential as a source of organic mulch, animal feed, and raw material for bioenergy. Utilizing agricultural waste as mulch can improve soil quality and crop yields, while its use as animal feed supports the integration of agricultural and livestock systems. In the context of energy, converting waste into biogas and biofuel offers an effective solution. Conclusion: This study emphasizes the importance of integrated and sustainable agricultural waste management to minimize negative impacts and optimize its economic potential. Novelty/Originality of this article: By providing a comprehensive analysis of the characteristics and impacts of agricultural waste, this study offers insights into the importance of a holistic approach to agricultural waste management to support sustainable agriculture.